Pre-retirement training among lecturers in Universiti Malaysia Sarawak (UNIMAS) : A case study - Farrid Moustaffa, Bin Janilabidin (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study aims to examine the pre-retirement training among lecturers in UNIMAS. In this study, topics such as financial management, time management, and healthcare are related to pre-retirement training. This study uses the case study design engaging the survey method. This study involves five informants purposively sampled from Universiti Malaysia Sarawak in Kota Samarahan, Sarawak. An open-ended questionnaire is used to collect data. The findings identify that financial management, time management, and health care are positively related to retirement. This study contributes to a better understanding of retirement among lecturers.